Novel KCNJ10 Compound Heterozygous Mutations Causing EAST/SeSAME-Like Syndrome Compromise Potassium Channel Function - Zhang, Hongfeng; Zhu, Lin; Wang, Fengpeng; Wang, Ruimin; Hong, Yujuan; Chen, Yangqin; Zhu, Bin; Gao, Yue; Luo, Hong; Zhang, Xian; Sun, Hao; Zhou, Ying; et al. (Frontiers in Genetics, 2019)
Inwardly rectifying K+ channel 4.1 (Kir4.1), encoded by KCNJ10, is a member of the inwardly rectifying potassium channel family. In the brain, Kir4.1 is predominant in astrocytic glia and accounts for the spatial buffering of K+ released by neurons during action potential propagation. A number of studies have shown that mutations in KCNJ10 are associated with SeSAME/EAST syndrome, which is characterized by seizures, ataxia, sensorineural deafness and electrolyte imbalance. Herein, we identified two siblings presenting with seizures and motor delays in one outbred kindred. Customized targeted-exome sequencing showed that both affected siblings are compound heterozygous for two KCNJ10 missense mutations (NM_002241.4: c.601G>A: p.A201T and c.626T>C: p.I209T). Prediction tools suggested that both amino acid substitutions were deleterious or disease causing. Further functional studies showed that Chinese hamster ovary (CHO) cells expressing either A201T and/or I209T Kir4.1 channels exhibited lower K+ currents, indicating compromised Kir4.1 biological function. Intriguingly, the A201T but not the I209T mutation decreased total and cell surface Kir4.1 levels. Kir4.1 channels with the A201T mutation were unstable and degraded through lysosomal pathway. In conclusion, these data indicated that both A201T and I209T mutations disrupt Kir4.1 activity and are the cause of SeSAME/EAST-like syndrome in the siblings.